Scaling up radio and ICTs for enhanced extension delivery and development impact: Quantitative baseline report - Ragasa, Catherine; Carrillo, Lucia; Balakasi, Kelvin (International Food Policy Research Institute, 2022)
This report summarizes the baseline data that describe the rural population of five districts in Malawi targeted in the Scaling up Radio and ICTs for Enhanced Extension Delivery (SRIEED) II project that started in 2020 and ends in 2024. It also provides the impact evaluation strategy for the overall project as well as a causal impact evaluation of a major component of the project (impact ICT hubs).